If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6v=5v+3
We move all terms to the left:
-6v-(5v+3)=0
We get rid of parentheses
-6v-5v-3=0
We add all the numbers together, and all the variables
-11v-3=0
We move all terms containing v to the left, all other terms to the right
-11v=3
v=3/-11
v=-3/11
| 4(2x-3)=18-2x | | 14=f(2) | | 3/5x-14=-31 | | C•1=c | | 10n=6+7n | | 49=t(7) | | -2(x-4)+4(2x-4)=1+2x-1 | | –10−10+7d=10+10d | | -r+9=-4r | | 11.25=1.5(2x+7) | | 8.2t+3=12.5t+10 | | z2−8z+25=0 | | 10x+5=12+1 | | 2/3x-5=-1/3x=2 | | 3h=-9+4h | | x/3+1.1=-6.4 | | 5m=0.45 | | 95+145+101+(x+1)+x=360 | | 8n=56. | | –4r+2=–3r−6 | | 5.5t=32 | | 93b/7)-1=5 | | 7y-3y-9=51.20 | | -42=6(x+12) | | 3p+12=60 | | 12=2(6x–6) | | 6x-19=6(x-2)-7 | | 24m=48 | | 3x+90+x=90 | | 3x+90+x=80 | | 3/4(x)-1.7=-6.82 | | x÷4=28—x÷44=28—4x=7 |